2009
DOI: 10.1007/s10620-008-0704-1
|View full text |Cite
|
Sign up to set email alerts
|

Infection by CagA-Positive Helicobacter pylori Strains may Contribute to Alter the Sperm Quality of Men with Fertility Disorders and Increase the Systemic Levels of TNF-α

Abstract: This study was aimed to address the possibility that Helicobacter pylori infection may play a detrimental role in semen quality of men with idiopathic infertility. Infection by H. pylori and by strains expressing CagA was determined in 80 male infertile patients by Western blotting and ELISA. Semen analysis was performed by light microscopy and transmission electron microscopy quantitatively elaborated (fertility index, immaturity, necrosis, and apoptosis percentages). Systemic levels of IL-6 and TNF-alpha wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 23 publications
8
42
1
Order By: Relevance
“…It has been shown that infection with CagA-positive H. pylori strains in women is linked to an increased potential of early abortion and in men is related to poor sperm quality (6,26,27). Although several transmission pathways have been identified for this microorganism, the definite route of transmission is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that infection with CagA-positive H. pylori strains in women is linked to an increased potential of early abortion and in men is related to poor sperm quality (6,26,27). Although several transmission pathways have been identified for this microorganism, the definite route of transmission is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Based on available literature, a H. pylori infection model, related to prostate and bladder diseases, has been hypothesized (5). In addition, an association between infection with H. pylori and poor sperm quality in infertile men, compared to uninfected individuals has been reported (6).…”
Section: Introductionmentioning
confidence: 99%
“…that they are infected by bacterial genotypes endowed with an increased inflammatory potential), have a) increased systemic levels of tumor necrosis factor-alfa, a proinflammatory cytokine that may cause sperm damage; b) reduced sperm motility in vitro and c) a greater number of necrotic and apoptotic spermatozoa in their ejaculates [4]. The partial results of still another unpublished study from…”
Section: Lettermentioning
confidence: 99%
“…that they are infected by bacterial genotypes endowed with an increased inflammatory potential), have a) increased systemic levels of tumor necrosis factor-alfa, a proinflammatory cytokine that may cause sperm damage; b) reduced sperm motility in vitro and c) a greater number of necrotic and apoptotic spermatozoa in their ejaculates [4]. The partial results of still another unpublished study from *Address correspondence to this author at the Department of Biomedical Sciences, University of Siena, Policlinico S. Maria alle Scotte, V.le Bracci, 53100 Siena, Italy; Tel: +39 0577 233511; Fax: +39 0577 233527; E-mail: mailto:elena.moretti@unisi.it our group show that H. pylori infection may regulate the seminal levels of ghrelin, a hormone endowed with antiinflammatory properties [5] and involved in reproduction [6], suggesting that the infection may influence the semen concentration of hormones.…”
Section: Lettermentioning
confidence: 99%
“…suggested to be an important cause of infertility [11,12]. We therefore propose to include the test for pathogenic strains of H. pylori when treating cases of infertility.…”
Section: Regardless Of the Mechanisms H Pylori Infection Has Beenmentioning
confidence: 99%